The role of community engagement toward ensuring healthy lives: a case study of COVID-19 management in two Ghanaian municipalities - Aberese-Ako, Matilda; Doegah, Phidelia Theresa; Kpodo, Lebene; Ebelin, Wisdom; Kuatewo, Mawulom; Baba, Atubiga Alobit; Kpordorlor, Atsu Godsway; Lissah, Samuel Yaw; Kuug, Anthony Kolsabilik; Ansah, Evelyn (Frontiers in Public Health, 2024)
Introduction Community engagement is one of the important requirements for strengthening health delivery in communities in a bid to achieve sustainable development goal 3, target 3.3 (SDG 3.3). The World Health Organization has strongly encouraged the use the five levels of community engagement, which are informing, consulting, planning, collaborating, and empowering communities in order to build resilience and to enable them contribute to the fight against diseases and for the uptake of health interventions. This study sought to explore and describe from the view of government institutions in Ghana how they engaged communities in COVID- 19 management and vaccine acceptance and how the communities within two municipalities also perceived the engagement process as well as the lessons that can be learned in engaging communities to deal with other health challenges and interventions toward the attainment of SDG 3 target 3.3. Materials and methods This case study qualitative research project employed in-depth interviews among 36 respondents composed of government officials (the Ghana Health Service (GHS), the Information Services Department (ISD), the National Commission on Civic Education (NCCE) and two Municipal Assemblies), and community leaders and 10 focus group discussions among 87 men and women most of whom were natives and some migrants in two administrative municipalities in Ghana. Data were collected from June to September 2021. Audio interviews were transcribed and uploaded to Nvivo 12 to support triangulation, coding, and thematic analysis. Ethical approval was obtained from the University of Health and Allied Sciences’ Research Ethics Committee and all COVID-19 restrictions were observed. Results The findings revealed that all the four government institutions educated and informed the communities within their municipalities on COVID-19 management and vaccine acceptance. However, the Ghana Health Service was the most effective in the engagement spectrum of the other four; consulting, involving, collaborating, and empowering communities in the process of COVID-19 management and vaccine acceptance. The GHS achieved that through its CHPS program, which ensured a decentralized health service provision system with multiple programs and leveraging on its multiple programs to reach out to the communities. Government institutions such as the NCCE and the ISD faced challenges such as limited funding and support from the government to be able to carry out their tasks. Additionally, they were not involved with the communities prior to the pandemic and for that matter, they did not have access to community systems such as committees, and existing groups to facilitate the engagement process. Discussion Using communities to support Ghana’s attainment of the SDG 3 target 3.3 is possible; however, the government needs to provide funds and resources to the institutions responsible to enable them to carry out community engagement effectively. Also, promoting decentralization among institutions can strengthen community engagement processes. It is important that state institutions continue to strategize to empower communities in order to promote their participation in healthcare interventions and in the fight against infectious diseases in Ghana.